Three Early Seventeenth-Century Tradesmen’s Accounts, rendered to the Earl and Countess of Angus, 1618-1628 - Scott-Moncrieff, Robert (Proceedings of the Society of Antiquaries of Scotland, 1911)
The accounts are amongst the earliest, if not the earliest, detailed tradesmen's accounts which survive. They are for clothing materials supplied to the Earl of Angus and his family during the years 1618, 1627, and 1628. The accounts are reproduced in full.